2022
DOI: 10.1021/acscatal.1c05608
|View full text |Cite
|
Sign up to set email alerts
|

Desulfonylative Transformations of Sulfones by Transition-Metal Catalysis, Photocatalysis, and Organocatalysis

Abstract: Sulfones are common, readily available reagents that have recently attracted attention as versatile reagents for cross-coupling reactions. This Review summarizes advances in desulfonylative transformations of sulfones affected by molecular catalysis, including transition-metal catalysts, photocatalysts, and organocatalysts. In addition to catalyst choice, the design of the sulfonyl group is a critical factor to control reactivity. The concepts presented herein will provide new strategies to construct diverse m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(41 citation statements)
references
References 143 publications
1
38
0
2
Order By: Relevance
“…Since Wenkert's group first realized nickel-catalyzed C-S bond cleavage of sulfones in 1979, 89 this strategy has been widely explored and applied. 90 In 2012, Li's research group developed the cross-coupling of Ts-alkanes and Grignard reagents by means of Kumada coupling (Scheme 55). 91 A series of alkenes and aryl ketones were successfully synthesized using this strategy.…”
Section: C-s Bond Cleavage Of Sulfonesmentioning
confidence: 99%
“…Since Wenkert's group first realized nickel-catalyzed C-S bond cleavage of sulfones in 1979, 89 this strategy has been widely explored and applied. 90 In 2012, Li's research group developed the cross-coupling of Ts-alkanes and Grignard reagents by means of Kumada coupling (Scheme 55). 91 A series of alkenes and aryl ketones were successfully synthesized using this strategy.…”
Section: C-s Bond Cleavage Of Sulfonesmentioning
confidence: 99%
“…Solar energy is considered to be a clean and renewable energy source and can be utilized through photocatalysis, photothermal conversion, photovoltaic, and so on. Among them, photothermal conversion technology is the most direct application of solar energy.…”
Section: Introductionmentioning
confidence: 99%
“…Building on the work of our group and others with regards to the application of sulfones in catalysis, we show that visible-light photoredox catalysts can be employed to promote the reductive desulfonylation of tertiary alkylsulfones and their reaction with gem -difluoroalkenes (Scheme c). Previous reports from our group, the Sengoku/Yoda group, and the Chatterjee group have shown that carbon radicals can be generated from alkylsulfones either through single electron reduction promoted by Zn and 1,10-phenanthroline (phen) or visible-light-induced reduction.…”
Section: Introductionmentioning
confidence: 92%